Evaluación de la viabilidad celular de las células madre de la papila apical expuestas al biocerámico MTA (Mineral Trióxido Agregado). Estudio ex vivo (2021)
The Bioceramic MTA on days 3, 5 and 7 altered the morphology of the cells when it was subjected to the study concentrations. At the concentrations of 0.5 mg / ml, 0.25 mg/ ml and 0.125 mg / ml, adhered cells were observed in all concentrations without connections or branches or the typical fibroblast morphology and decreased cell population. Regarding cell viability, in the studies of trypan blue and WST-1 on days 3, 5, and 7, it was evidenced that all the proposed MTA concentrations negatively affected cell viability. Cell proliferation analysis at all concentrations showed that exponential growth was observed on days 1 and 3, contrary to days 5 and 7, which were affected.